2022
DOI: 10.1016/j.jiac.2021.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia accompanied by COVID-19 successfully treated using cyclosporine

Abstract: A 67-year-old Japanese man was admitted to our hospital with severe coronavirus disease 2019 (COVID-19) in March 2020. Mechanical ventilation was initiated 8 days after admission, due to severe respiratory failure. Multiple severe complications such as liver dysfunction, arrhythmia, brain infarction, and venous thromboembolism were also observed. We initially diagnosed Coombs test-positive warm autoimmune hemolytic anemia. Corticosteroids proved ineffective and anemia worsened with severe erythroid hypoplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In our case, AIHA and PRCA were induced after a low-grade symptom of COVID-19 associated with mild fever, suggesting that slight or asymptomatic COVID-19 infection could cause such hematological disturbances. Although previous reports on COVID-19-associated PRCA that were resistant to PSL treatment and recovery after the administration of cyclosporine [ 15 ] or tacrolimus [ 13 ] were published, our case and the case by Karrat et al [ 12 ] showed a good response to PSL as shown in Table 2 . The case by Ghimire et al [ 14 ] also showed a response to dexamethasone.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In our case, AIHA and PRCA were induced after a low-grade symptom of COVID-19 associated with mild fever, suggesting that slight or asymptomatic COVID-19 infection could cause such hematological disturbances. Although previous reports on COVID-19-associated PRCA that were resistant to PSL treatment and recovery after the administration of cyclosporine [ 15 ] or tacrolimus [ 13 ] were published, our case and the case by Karrat et al [ 12 ] showed a good response to PSL as shown in Table 2 . The case by Ghimire et al [ 14 ] also showed a response to dexamethasone.…”
Section: Discussionmentioning
confidence: 55%
“…Our case was associated with simultaneous occurrence of AIHA and PRCA after COVID-19. As per our search, simultaneous occurrence of AIHA and PRCA [ 14 , 15 ], or occurrence of PRCA [ 12 , 13 ] after COVID-19 have rarely been reported. Those reported patients including our case are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations